IMPLEMENTATION OF THE MERDEKA CURRICULUM POLICY IN IMPROVING THE QUALITY OF LEARNING AT SD NEGERI 1 TUGUPAPAK - Apri Pil Bahrul Ulum; Nasrurro Fingudin; Bagus Sudrajat; Iman Wahyudi; Sri Andayani (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum policy in improving the quality of learning at SD Negeri 1 Tugupapak. This study was motivated by the need to improve the quality of education through a more flexible and student-centered learning approach. The method used is a qualitative approach with a case study design. Data collection techniques were conducted through observation, interviews, and documentation involving teachers and school officials. The results of the study indicate that the implementation of the Merdeka Curriculum contributes positively to improving the quality of learning, particularly in enhancing student engagement, learning flexibility, and the application of contextual learning. However, there are several challenges in its implementation, such as limited teacher readiness, variations in student abilities, and limited learning facilities. Supporting factors such as teacher commitment, institutional support, and adaptive learning strategies also play a role in the success of policy implementation. This study concludes that the effective implementation of the Merdeka Curriculum requires continuous teacher capacity building, the provision of adequate resources, and a collaborative learning environment.